2017
DOI: 10.1002/jbm.a.35983
|View full text |Cite
|
Sign up to set email alerts
|

Modified porous scaffolds of silk fibroin with mimicked microenvironment based on decellularized pulp/fibronectin for designed performance biomaterials in maxillofacial bone defect

Abstract: Maxillofacial bone defect is a critical problem for many patients. In severe cases, the patients need an operation using a biomaterial replacement. Therefore, to design performance biomaterials is a challenge for materials scientists and maxillofacial surgeons. In this research, porous silk fibroin scaffolds with mimicked microenvironment based on decellularized pulp and fibronectin were created as for bone regeneration. Silk fibroin scaffolds were fabricated by freeze-drying before modification with three dif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 51 publications
0
11
0
Order By: Relevance
“…Owing to the shortage of suitable donors and rejection rates, a wide range of studies have considered the decellularization of human lung tissue as an initiative for developing personalized lung grafts as a possible future option. , Many other studies reported the decellularization of human tissues (e.g., gingiva, dental pulp, Schneiderian membrane, small intestine, kidney, bladder, testis, cornea, vocal folds, and peripheral nerves) to obtain human tissue-derived dECM for a wide range of tissue engineering applications. Some of the tissues (e.g., the umbilical cord, placenta, and amniotic membrane) are considered waste products after childbirth, and because they are easily available, inexpensive, and without ethical concerns, these may be considered as ideal candidates to be used as decellularized biomaterials for tissue engineering. , Taken together, in the most recent years, much attention has been drawn toward the utilization of human sources due to increased awareness about the importance of the ECM specificity, in terms of architectural, biomechanical, and bioactivity characteristics.…”
Section: Decellularizationmentioning
confidence: 99%
“…Owing to the shortage of suitable donors and rejection rates, a wide range of studies have considered the decellularization of human lung tissue as an initiative for developing personalized lung grafts as a possible future option. , Many other studies reported the decellularization of human tissues (e.g., gingiva, dental pulp, Schneiderian membrane, small intestine, kidney, bladder, testis, cornea, vocal folds, and peripheral nerves) to obtain human tissue-derived dECM for a wide range of tissue engineering applications. Some of the tissues (e.g., the umbilical cord, placenta, and amniotic membrane) are considered waste products after childbirth, and because they are easily available, inexpensive, and without ethical concerns, these may be considered as ideal candidates to be used as decellularized biomaterials for tissue engineering. , Taken together, in the most recent years, much attention has been drawn toward the utilization of human sources due to increased awareness about the importance of the ECM specificity, in terms of architectural, biomechanical, and bioactivity characteristics.…”
Section: Decellularizationmentioning
confidence: 99%
“…Tissue engineering is recognized as a promising approach in many fields of dentistry; however, the interest for dental pulp decellularization is quite recent. Sangkert and Collaborators [236,237] were the first authors considering decellularization of dental pulp (half-segmented teeth) by collagenase and dispase. The process succeeded in obtaining a solution that was used at a concentration of 0.1 mg/mL in 0.1% NaClO in combination with collagen or fibronectin to coat silk supports.…”
Section: Dental Pulpmentioning
confidence: 99%
“…In recent years, the combination of acellular ECM and composite materials has shown to play an important role in synergistically promoting the regeneration of related maxillofacial tissues. For instance, the combined application of a decellularized pulp tissue, fibronectin, and a silk fibroin scaffold can promote the formation of a new bone [70,71] . The mixture of acellular bone matrix, hydroxyapatite, and extracellular vesicles is more beneficial to the repair of rabbit mandibular bone defect models [72] …”
Section: Research Progress In Plastic and Reconstructive Surgerymentioning
confidence: 99%
“…For instance, the combined application of a decellularized pulp tissue, fibronectin, and a silk fibroin scaffold can promote the formation of a new bone. [70,71] The mixture of acellular bone matrix, hydroxyapatite, and extracellular vesicles is more beneficial to the repair of rabbit mandibular bone defect models. [72] Compared with bones, the reconstruction of facial muscles seems more complicated because it involves multiple functions, including speaking, chewing, expressions, etc.…”
Section: Facementioning
confidence: 99%